Peningkatan Pengetahuan dan Keterampilan Keluarga dalam Menerapkan Metode Keperawatan Edukatif untuk Penderita TB Paru - Aniharyati; Muhtar (CV. CENDIKIA JENIUS INDONESIA, 2026)
This community service program aims to evaluate the knowledge and skills of families in implementing supportive-educative nursing methods to improve medication adherence in patients with pulmonary tuberculosis (TB). Pre-test and post-test methods were used to compare the effectiveness of this educational intervention. The training involved providing information about pulmonary TB, the importance of adherence to treatment, and family support. The analysis revealed a significant increase in respondents' knowledge, from 10% in the good category before the intervention to 73.3% afterward; and in skills, from 10% to 90%. This intervention demonstrates that family participation and support influence the treatment outcomes of pulmonary TB patients, with active interaction in the learning process. This study emphasizes the importance of the family's role in improving patient adherence to treatment regimens and reducing the social stigma associated with this disease. In conclusion, by improving knowledge and skills through a supportive-educational nursing approach, families can serve as key supporters in the care of pulmonary TB patients. These findings are expected to serve as a reference for family-based intervention strategies in TB control, as well as provide a basis for developing a more inclusive and comprehensive health education model.